If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2y + 6x = 12 Reorder the terms: 6x + -2y = 12 Solving 6x + -2y = 12 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2y' to each side of the equation. 6x + -2y + 2y = 12 + 2y Combine like terms: -2y + 2y = 0 6x + 0 = 12 + 2y 6x = 12 + 2y Divide each side by '6'. x = 2 + 0.3333333333y Simplifying x = 2 + 0.3333333333y
| 6w-2=28 | | 8-5(3+8a)=-327 | | 2[a-5]=14 | | 3=9-2c | | 3tg^4x-10tg^2x+3=0 | | 4x+32-2x+16=2 | | 12[3+a]=48 | | 7-6(8x+2)=-293 | | y+11=5y+29 | | 0.5(3x-1)+0.5x=2x-0.5 | | 12[x+11]=156 | | x-0.1=0.9 | | 4.8x-8.6=20.2 | | 5(4b+3)=135 | | (12)=-3x+10 | | 1485=-11(9x+9) | | 14x-8x=42 | | -15=.5[x+6] | | 5(5p+4)+4(3p+2)= | | 2n+25=4n+23 | | 190/50 | | 7w+2w=45 | | y-10=-x+2 | | x-3.6=1.4 | | 5k-4=2k+11 | | -5+8k=7k+4-7 | | Ab/c=xy/z | | 3x(2xy)(-3x^5y^2)= | | 15/6xt=81 | | X=5x-2x+3x-4x+5x | | 6^1*0+2%2 | | v-2=10-v |